Kesiapan Mahasiswa melaksanakan Praktek Lapangan Kependidikan: Pengaruh Perkuliahan Pedagogi Kejuruan dan Metode Mengajar Khusus - Syah, S Nurhilma; Elfizon, Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Students of the Electrical Engineering education study program have poor readiness in carrying out educational field practices. Vocational Pedagogy and Special Teaching Methods are courses that equip students to be better prepared to carry out educational field practice. This research aims to examine the effect of Vocational Pedagogy and Special Teaching Methods lectures on students' readiness to carry out Educational Field Practices. The type of research used in this research is quantitative research with 2 independent variables, namely X1 (Vocational Pedagogy Lectures), X2 (Special Teaching Methods Lectures), and Y (Readiness to Carry Out Educational Field Practices). This research uses quantitative correlation techniques using observation methods and distributing questionnaires which will be tested for validity and reliability. In this research, the data analysis technique consists of 3 parts, namely Description Analysis, Analysis Requirements Test, and Hypothesis Testing. Based on the results of the research and discussions that have been carried out, there are three things that can be concluded. First, there is a significant influence from Vocational Pedagogy lectures on students' readiness to carry out Educational Field Practices with a quite high percentage. Second, there is a significant influence of Special Teaching Method lectures on students' readiness to carry out Educational Field Practices with a quite high percentage. Third, there is a significant influence of Vocational Pedagogy Lectures and Special Teaching Methods together on students' readiness to carry out Educational Field Practices with a quite high percentage.